Penerapan Nilai-Nilai Filsafat Ekonomi Islam dalam Pengambilan Keputusan Ekonomi : Studi Kualitatif - Ahmad Wahyudi Zein; Popi Dea Ananda; Muhammad Iqbal; Salsabila Sofiya Wardani (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to examine the application of Islamic economic philosophy values in economic decision-making in Indonesia. Islamic economic philosophy, based on the teachings of the Qur’an and Hadith, emphasizes principles of justice, balance, and public welfare. Using a qualitative approach, this research gathers data through in-depth interviews with practitioners, entrepreneurs, and academics involved in Islamic economics. The findings reveal that values such as justice in wealth distribution, prohibition of usury (riba), and the importance of meeting societal needs serve as key guidelines in economic decision-making. Moreover, the application of concepts like zakat, charity (sedekah), and transparent transactions are also essential factors in ensuring a fair and sustainable economic system. The study also identifies challenges in implementing these values, such as low public awareness and lack of adequate supporting infrastructure. However, there is significant potential to integrate these Islamic economic values into modern economic practices to create a more humane and just economic system. Therefore, strengthening education and understanding of Islamic economics is crucial to support better economic decision-making.